Early detection of microcirculatory changes using simultaneous heated and unheated transcutaneous blood gas monitoring: a proof-of-concept study in a porcine lipopolysaccharide model of systemic inflammation - Maud A. Hoofs; Louwrina H. te Nijenhuis; Norani H. Gangaram-Panday; Patricia A. C. Specht; Egbert G. Mik; Floor A. Harms; Irwin K. M. Reiss; Willem van Weteringen (Frontiers in Medicine, 2026)
Introduction Early detection of microcirculatory failure in septic patients has the potential to improve clinical outcomes. The microcirculation regulates the oxygen (O 2 ) supply and carbon dioxide (CO 2 ) washout in tissues and changes early during severe inflammation and sepsis. Transcutaneous blood gas sensors measure tissue O 2 and CO 2 levels at the skin surface, or when warmed use the vasodilatory response to approximate arterial levels. In addition to differences in measured O 2 and CO 2 values, systemic inflammation is likely to affect this vasodilatory effect of skin warming. This study investigated whether continuous comparison of heated and unheated transcutaneous blood gas monitoring could early detect microcirculatory changes using a porcine lipopolysaccharide (LPS) model of systemic inflammation. Methods Thirty female Yorkshire x Norwegian Landrace pigs were subdivided into three study groups (control, LPS, and LPS with fluid resuscitation) and received LPS or saline control. Transcutaneous CO 2 (tcPCO 2 ) and O 2 (tcPO 2 ) were continuously and simultaneously measured using a heated (43 °C) and unheated (37 °C) transcutaneous sensor (Sentec OxiVenT™) at the porcine ear. Arterial blood gas measurements (PaCO 2 and PaO 2 ) were performed at baseline and 1, 2, and 3 h after LPS administration. At each time point, tcPCO 2 , tcPO 2 , and differences between transcutaneous and arterial blood gas measurements were determined. In addition, the unheated-heated tcPCO 2 difference and the ratio between heated tcPCO 2 and tcPO 2 (tcPCO 2 /tcPO 2 ) were calculated. Results After LPS administration, a significant increase in heated tcPCO 2 and a significant decrease in tcPO 2 and tcPO 2 /tcPCO 2 were observed. This resulted in a significant decrease in the unheated-heated tcPCO 2 difference from 22.1 [18.8–33.2] to 0.7 [−8.3–8.8] mmHg in the LPS group, and from 23.0 [16.9–23.9] to −1.2 [−6.6–2.0] mmHg in the resuscitation group, while it remained 6.5 [3.1–9.8] mmHg in the control group. PaCO 2 and PaO 2 did not show large changes. Conclusion Heated tcPCO 2 , tcPO 2 , unheated-heated tcPCO 2 , and tcPO 2 /tcPCO 2 as observed using transcutaneous blood gas monitoring are promising parameters for early detection of microcirculatory changes during severe infections. In future studies, simultaneous heated and unheated transcutaneous measurements should be further explored in both healthy and septic patients.